2013
DOI: 10.4081/mm.2013.2250
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of sexually transmitted diseases and main methodological implications

Abstract: INTRODUZIONELe infezioni sessualmente trasmesse (MST) hanno un'incidenza di circa 340 milioni di nuovi casi ogni anno (48); se non trattate, molte di esse possono produrre infezioni con gravi complicanze, quali infertilità, aborti precoci e malattie neonatali di grado severo (18,24). I costi socio-economici di queste infezioni e delle loro complicanze sono elevati; lo screening per la prevenzione primaria del cancro della cervice e gli interventi per il trattamento e follow-up delle neoplasie cervicali intraep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(54 reference statements)
1
2
0
Order By: Relevance
“…We found that the prevalence of U.parvum in the area of Prato was about 34%, according to data previously reported in Tuscany (6). For the other microorganisms the prevalence, in the same area, was similar to that found in the year 2011 (1).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that the prevalence of U.parvum in the area of Prato was about 34%, according to data previously reported in Tuscany (6). For the other microorganisms the prevalence, in the same area, was similar to that found in the year 2011 (1).…”
Section: Discussionsupporting
confidence: 90%
“…Data about the prevalence of U.parvum in Italy are scarce (6). In 2012 a PCR real time method able to differentiate U. urealyticum and U. parvum has been introduced in our laboratory for the routine analysis of urogenital samples.…”
Section: Introductionmentioning
confidence: 99%
“…NAATs have a significantly lower turnaround time (they can be easily automated, and the time to result is significantly lower than that of traditional approaches), they allow the detection of organisms which cannot be grown in culture, and they have a significantly higher sensitivity (a dramatically relevant advantage for asymptomatic infections where the organisms' load is low) [61,62]. Due to their high sensitivity, NAATs are an invaluable tool for detecting extragenital infections, as shown in the case of rectal or pharyngeal gonorrhea in men [63].…”
Section: Nucleic Acid Amplification Tests (Naats) and Detectionmentioning
confidence: 99%